(untitled) (SNPRC Journal, 2023)
Foreign trade plays a crucial role in fostering economic growth through increasing innovation, efficiency, market expansion, and optimum use of resources. This paper attempts to deal with the effect of foreign trade on the economic growth of Nepal. This study is based on secondary data for the period of FY 1974/75 to 2021/22. The Augmented Dickey-Fuller (ADF) test is used to check the stationary of variables. The Auto Regressive Distributed Lag (ARDL) bound testing approach has been applied to establish the long-run relationship between dependent variables: GDP and independent variables, i.e. export and imports. Similarly, an Error Correction Model (ECM) has been conducted to check the speed of correction of short-term fluctuations to the long-run equilibrium. This study found a positive relationship between exports and the GDP of Nepal. However, there is a negative relationship between GDP and imports in Nepal. The negative and significant value of the ECM coefficient explains the equilibrium in the long run, even though there are some fluctuations in the short run. For high economic growth, Nepal should make a proper balance between an export growth strategy and an import substitution policy in foreign trade.